(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
This study aimed to determine how the function of the village government in the implementation of development in the village of West Soro, Kempo District, Dompu Regency. The method used descriptive qualitative suppression method so that it could explain the object of this study in the office of West Soro Village, Kempo District, Dompu Reency. Data and information were obtained from informants. Data collection techniques were direct observations at research sites, depth interviews, and documentation. Data analysis techniques used data reduction which summarized and focused on the important things and conclusions. The result of this study showed that the function of the village government had been done effectively because there were several things that support them. They were the process of regulation, service, empowerment and in the process of development implantation.